The Role of Stakeholders in The Development of Tourism Attraction at Mertasari Beach, Sanur - Ismadwijayanthi, Gusti Ayu Maharani; Mertha, I Wayan; Lilasari, Luh Nyoman Tri (Journal of Applied Science in Tourism Destination, 2023)
This study aims to determine the stakeholders who have a role in the development of DTW (Tourism Attractiveness) Mertasari Beach. DTW Mertasari Beach is located in Sanur Kauh Village. Informants in this study were determined by purposive sampling. This study used data collection techniques, by conducting observations, in-depth interviews, documentation and literature studies. The results of data collection were then analyzed using qualitative descriptive analysis techniques. The results of this study concluded that Bendesa Adat Intaran, Intaran BUPDA, Muntig Siokan Inspiration Park and Pokdarwis Sanur Kauh Village are categorized as primary stakeholders. Secondary stakeholders consist of The Perbekel Desa Sanur Kauh, Bali State Polytechnic and Tribun Bali. The Denpasar Tourism Department, categorized as a key stakeholder. Then the classification of stakeholders based on their roles, as policy creators are Bendesa Adat Intaran and Denpasar Tourism Department. Bendesa Adat Intaran and Intaran BUPDA are acted as coordinators as well, then as facilitators are Muntig Siokan Inspiration Park, Perbekel Desa Sanur Kauh and the Denpasar Tourism Department. Inspiration Park Muntig Siokan and BUPDA Intaran as implementers and then as an accelerators are Perbekel Desa Sanur Kauh, Bali State Polytechnic, Pokdarwis Sanur Kauh Village and Tribun Bali.